Septic arthritis of the wrist: A case of Parona space abscess in a rheumatoid arthritis patient with Charcot wrist - Zainab Mashaalla Ahmed, MB, BCh, BAO; Huda Alsahlawi, MD; Rola Husain, MB, BCh, BAO (Radiology Case Reports, 2024)
Closed-space hand infections are considered an emergency requiring prompt management to avoid debilitating consequences and potential morbidity. Septic arthritis of the wrist is particularly uncommon in comparison to the large joints that are usually affected. We report a case of a 64-year-old female with known rheumatoid arthritis and neuropathic wrist, with superimposed septic arthritis of the wrist, complicated by abscess formation. Ultrasound and Magnetic resonance imaging revealed spread of infection to the midpalmar region and the space of Parona. Although collections in this space are extremely rare, if left untreated, they may lead to permanent disability. Incision and drainage of the abscess along with synovectomy of the affected wrist joint was performed. Streptococcus pneumoniae was the causative organism, despite the fact that Non-gonococcal and Staphylococcus aureus bacteria are the main causative agents of septic arthritis in adults.